Sosialisasi Halal untuk Pengajuan Sertifikasi Halal Self Declare dan Peningkatan Kesadaran Konsumen terhadap Produk Halal - Siswara, Hamzah Nata; Wulandari, Kartika; Huda, Khoirul; Saputro, Tri Hadi; Dana, Aldi Arma (Jurnal Pengabdian Masyarakat Charitas, 2023)
Halal certification is a Recognition of the halal status of a product issued by the Halal Product Guarantee Organizing Agency (BPJPH) based on halal regulations (written halal fatwa) issued by the Indonesian Ulema Council (MUI). Activities to socialize halal certification and increase consumer awareness of halal products were carried out at SMKN Ngambon, Bojonegoro. This activity was carried out based on the pie susu product developed by SMKN Ngambon and requiring halal certification. Apart from that, it is important to socialize halal products to the nation's young generation. The socialization method used is an lecture and interactive discussion method by displaying presentation slides containing material. Participants in the socialization activities were vocational school students aged 15-20 years. Halal certification outreach activities at SMKN Ngambon Bojonegoro provide insight into halal products in daily life. This activity also increases awareness of the importance of halal certification for food products circulating around. Participants' ignorance of halal products.